GENDER ROLES AS SEEN IN ‘BARBIE’ MOVIE BY GRETA GERWIG - Al Musdalifa, Nasya; Tri Widyahening, Ch. Evy (English Education Department Slamet Riyadi University Surakarta, 2025)
The objective of this research was to analyze how gender roles seen in the movie ‘Barbie’. This research is classified as a qualitative research type using a descriptive approach. The data from this study comes from ‘Barbie’ movie and script. Then, in collecting data the researcher used documentation by watching the movie and reading the script. In analyzing data, the researcher used interactive data analysis by Miles and Huberman. To find the research's validity, triangulation data and triangulation theory were used to check validation for the data. The result of the research showed that the ‘Barbie’ movie critiques societal norms and gender roles by contrasting Barbieland’s matriarchal utopia with the real world’s patriarchal limitations Keywords : Gender roles, Descriptive Qualitative, Barbie movie, Equality.